Development Of Antilock Braking System Based On Various Intelligent Control System - Aparow, Vimal Rau; Ahmad, Fauzi; Hassan, Muhammad Zahir; Hudha, Khisbullah (2012)
This paper presents about the development of an Antilock Braking System (ABS) using quarter vehicle model and control the ABS using different type of controllers. Antilock braking system (ABS) is an important part in vehicle system to produce additional safety for drivers. In general, Antilock braking systems have been developed to reduced tendency for wheel lock and improve vehicle control during sudden braking especially on slippery road surfaces. In this paper, a variable structure controller has been designed to deal with the strong nonlinearity in the design of ABS controller. The controllers such as PID used as the inner loop controller and fuzzy Logic as outer loop controller to develop as ABS model to control the stopping distance and longitudinal slip of the wheel.